QUALITATIVE AND QUANTITATIVE IDENTIFICATION OF CARBOHYDRATES IN COMMERCIAL YOGHURT PRODUCTS - Bagus Nurprialdi; Viesta Olivia Thahuurun Gani; Siti Halda; Peby Ardiani Pratama; Riong Seulina Panjaitan (Department of Pharmacy, Muhammmadiyah University of Sumatera Barat, 2022)
Yogurt is a healthy drink that has thick, acidic properties and a high nutritional content. Yogurt is made by adding bacteria to milk, which naturally contains a type of sugar (carbohydrate) called lactose.Qualitative testing methods for carbohydrates are the Molisch test, the iodine test, the Benedict test, the Barfoed test, the Seliwanoff test, and the osazon test. Meanwhile, in quantitative testing using the DNS method. The results of the Molisch carbohydrate qualitative test revealed that all four samples contained glucose. Polysaccharides were discovered in the six samples during the iodine test. The six samples tested negative for glucose in Benedict's test. One out of every six samples tested positive for monosaccharides in the Barfoed test. Both samples tested positive for fructose in the Seliwanoff test. In the osazone test, all yogurt samples contained glucose. Furthermore, the following results were obtained when determining the reducing sugar content of commercial yogurt samples: E (685 mg/mL); D (568.75 mg/mL); F (501.25 mg/mL); A (373.75 mg/mL); B (310 mg/mL); and C (210 mg/mL).